PENGEMBANGAN PROGRAM, STRATEGI, DAN PERANGKAT PENDUKUNG PEMBINAAN PERILAKU BERLITERASI SISWA SMA BERBASIS KEGIATAN ILMIAH - -, Suyono (Diksi, 2008)
Literacy-activity behavior, the behavior of doing literacy activities (i.e.,reading and writing), is very important for students in the completion of theirstudy, their advancement into a higher level of formal education, their preparationfor entrance into the world of work, and their life-long education in society.Therefore, such behavior needs to be developed in students at school.As an effort to develop it in a planned, systematic, and serious way, aprogram, strategy, and supporting facility for the development of senior highschool students' literacy-activity behavior based on scientific activities with anappeal and reliability already tested through developmental research have beendeveloped.Through empiric try-out and conceptual validation, the program, strategy,and supporting facility have been found to be capable of attracting students'interest and at the same time sufficiently reliable in improving students'awareness, motivation, skill, and fondness of doing literacy activities at schoolKeywords: literacy, literacy-activity behavior, development of literacy activitybehavior